Silk screen loaded noble metal catalyst prepared by ALD (Atomic Layer Deposition) method and application of silk screen loaded noble metal catalyst in catalysis of hydrogen combustion

Deposition of precious metal catalysts on the wire mesh support by atomic layer deposition method solves the problem of uneven loading of precious metal active components, realizes the preparation of high-efficiency hydrogen combustion catalyst, improves hydrogen conversion and heat transfer efficiency, and is suitable for a variety of supply Hot application.

CN119236924APending Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310782978.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing hydrogen combustion catalyst preparation methods, the load amount and particle size of the noble metal active components are difficult to accurately control, resulting in uneven catalyst activity. The preparation steps of the traditional impregnation method are cumbersome and cannot meet the needs of efficient hydrogen combustion.

Method used

Atomic layer deposition (ALD) method is used to deposit precious metal catalyst on the wire mesh support. By accurately controlling the reaction temperature, precursor flow rate and gas inlet time, uniform deposition and efficient load of precious metal oxides are achieved, and the hydrophobicity of the wire mesh is used and Thermal conductivity extends the life of the catalyst and promotes heat transfer inside the reactor.

Benefits of technology

The production of supported catalysts with controllable thickness and good uniformity of precious metal catalysts is achieved, and the hydrogen conversion rate and heat transfer efficiency of hydrogen combustion reaction are improved. The outlet temperature of the catalyst bed is increased, which is suitable for industrial and residential heating fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004311336610000061
    Figure BDA0004311336610000061
  • Figure BDA0004311336610000071
    Figure BDA0004311336610000071
Patent Text Reader

Abstract

The invention discloses a silk screen loaded noble metal catalyst prepared by an ALD (atomic layer deposition) method and application of the silk screen loaded noble metal catalyst in catalysis of hydrogen combustion. The catalyst is composed of a metal wire mesh carrier and a noble metal active component, the preparation method adopts an atomic layer deposition (ALD) method, the number of repeated cycles is 5-50, the mass loading amount of the noble metal in a wire mesh is 0.008-0.05 wt%, the noble metal is selected from at least one of platinum, palladium and ruthenium, the mesh number of the wire mesh is 10-500, and the thickness of the wire mesh is 0.1-1 mm; preferably, the mesh number is 50-250, and the thickness is 0.2-0.5 mm; and preferably, the mesh number is 100 to 200. According to the catalytic hydrogen combustion, a metal wire mesh loaded noble metal catalyst is placed in a fixed bed reactor into which hydrogen and air are introduced for a catalytic hydrogen combustion reaction, the hydrogen conversion rate reaches 100% at most, and the temperature of a bed outlet can exceed 100 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen catalytic combustion, and specifically relates to a wire mesh-loaded noble metal catalyst used in a hydrogen combustion process prepared by an atomic layer deposition (ALD) method. Background Art

[0002] The combustion of traditional fossil fuels leads to the emission of a large amount of greenhouse gases and pollutants into the atmosphere, causing a series of environmental problems such as global warming. Hydrogen energy, as a clean energy, has great development prospects in the global energy transformation. Compared with traditional fossil fuels, hydrogen energy has an extremely high mass energy density. The energy provided by hydrogen combustion is three times the energy generated by gasoline combustion, and the combustion is clean and no pollutants are emitted. Hydrogen combustion generally adopts the method of catalytic combustion. Compared with direct combustion, catalytic hydrogen combustion has higher safety and efficiency, the combustion process is easier to control, and no nitrogen oxides are produced. Among hydrogen combustion catalysts, precious metal catalysts have been widely studied due to their excellent hydrogen combustion catalytic activity. Precious metal catalysts are usually prepared by impregnation, but this method easily causes uneven distribution of active components, resulting in inconsistent catalyst activity. Atomic layer deposition (ALD) is a method that can accurately control the structure of catalyst active sites and local chemical environment at the atomic level, which is conducive to revealing the structure-activity relationship and reaction mechanism of catalysts. In general chemical vapor deposition (CVD), all reactants are injected at the same time, and surface reactions and gas phase reactions proceed simultaneously. In atomic layer deposition, reactants are injected in a certain order, and the deposition process is self-limiting, occurring only between reactants and the surface, not between reactants, so it can be deposited in atomic layers. During the deposition process, the thickness of the entire deposit is controlled by the number of deposition cycles (repetitions), and its advantages are that the deposition parameters are precisely controllable, and the deposition uniformity and repeatability are good. In recent years, ALD has shown great potential in the synthesis of advanced catalysts.

[0003] Invention patent CN113908831A discloses a hydrophobic catalyst for low-temperature catalytic combustion of hydrogen and a preparation method thereof. The catalyst includes an inner carrier, a loaded active layer and a hydrophobic layer. The hydrophobic layer is formed by self-assembly on the catalyst surface, which enhances the gas molecule mass transfer efficiency and water resistance, and increases the low-temperature activity of the catalyst. However, the preparation of the hydrophobic layer makes the preparation steps of the catalyst more complicated, and the impregnation synthesis method cannot accurately control the loading amount and particle size of the noble metal active component.

[0004] There is no related research report on the synthesis of hydrogen combustion catalysts using ALD technology. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a wire mesh-loaded precious metal catalyst for catalytic hydrogen combustion and a preparation method thereof. By using the ALD method to load precious metals onto the wire mesh catalyst, a loaded catalyst with controllable thickness and good uniformity can be obtained, and the carrier metal wire mesh used has certain hydrophobicity and good thermal conductivity, which can extend the service life of the catalyst and promote the transfer of heat inside the reactor.

[0006] In one aspect, the present invention provides a wire mesh-supported precious metal catalyst, wherein the mass loading amount of the precious metal in the wire mesh is ≥ 0.008%.

[0007] Preferably, the present invention provides a wire mesh-supported noble metal catalyst, wherein the mass loading amount of the noble metal in the wire mesh is 0.008wt%-0.05wt%.

[0008] Preferably, the present invention provides a wire mesh loaded with a precious metal catalyst, wherein the wire mesh has a mesh number of 10-500 and a thickness of 0.1-1 mm; preferably, the mesh number is 50-250 and the thickness is 0.2-0.5 mm; more preferably, the mesh number is 100-200 mesh.

[0009] Preferably, the present invention provides a wire mesh loaded with a precious metal catalyst, wherein the wire mesh is woven from at least one metal wire selected from stainless steel, aluminum, copper, nickel, titanium or silver.

[0010] Preferably, the present invention provides a wire mesh-supported precious metal catalyst, wherein the precious metal is selected from at least one of platinum, palladium and ruthenium.

[0011] In another aspect, the present invention further provides an atomic layer deposition method for preparing a wire mesh-supported noble metal catalyst, comprising the following steps:

[0012] (i) placing the screen in an atomic layer deposition reactor in advance, raising the temperature of the atomic layer deposition reactor to 250° C. and keeping it stable;

[0013] (ii) heating the noble metal precursor and passing the generated vapor into the atomic layer deposition reactor for 10-15 seconds at a flow rate of 10 mL / min;

[0014] (iii) using an inert gas at a flow rate of 500 mL / min to purge away the excess noble metal precursor that has not chemically reacted, as well as the byproducts CO2 and H2O generated by the reaction, for a purge time of 25-30 s;

[0015] (iv) introducing an oxidizing gas at a flow rate of 10 mL / min for a time of 10-15 s; (v) purging again with an inert gas at a flow rate of 500 mL / min for a time of 25-30 s;

[0016] (vi) Repeating steps (ii) to (v) several times in sequence to achieve layer-by-layer deposition of the noble metal oxide on the surface of the metal wire.

[0017] Preferably, the present invention also provides an atomic layer deposition method for preparing a wire mesh loaded with a precious metal catalyst, wherein the wire mesh in step (i) is woven from at least one metal wire selected from stainless steel, aluminum, copper, nickel, titanium or silver.

[0018] Preferably, the present invention also provides an atomic layer deposition method for preparing a wire mesh-loaded precious metal catalyst, wherein the wire mesh in step (i) has a mesh size of 10-500 and a thickness of 0.1-1 mm; preferably, the mesh size is 50-250 and the thickness is 0.2-0.5 mm; more preferably, the mesh size is 100-200 mesh.

[0019] Preferably, the present invention also provides an atomic layer deposition method for preparing a wire mesh-supported noble metal catalyst, wherein the noble metal in step (i) is selected from at least one of platinum, palladium and ruthenium.

[0020] Preferably, the present invention further provides an atomic layer deposition method for preparing a wire mesh-supported noble metal catalyst, wherein the noble metal precursor in step (ii) is an organic metal precursor containing a noble metal component.

[0021] Preferably, the present invention also provides an atomic layer deposition method for preparing a wire mesh-loaded precious metal catalyst, wherein the precious metal precursor described in step (ii) is an organic metal precursor containing a precious metal component, and the organic metal precursor is selected from at least one of trimethyl(methylcyclopentadienyl)platinum(IV), diacetylacetonatepalladium, and bis(ethylcyclopentadienyl)ruthenium(II).

[0022] Preferably, the present invention further provides an atomic layer deposition method for preparing a wire mesh-supported noble metal catalyst, wherein the oxidizing gas in step (iv) is selected from at least one of ozone and oxygen.

[0023] Preferably, the present invention also provides an atomic layer deposition method for preparing a wire mesh-loaded precious metal catalyst, wherein the inert gas in step (iii) and step (v) is a high-purity gas with a volume concentration of 99.999%, selected from at least one of nitrogen, helium, neon, argon, etc.

[0024] Preferably, the present invention further provides an atomic layer deposition method for preparing a wire mesh-supported noble metal catalyst, wherein the number of times steps (ii) to (v) are repeated in sequence in step (vi) is at least 5 times, preferably 5-50 times.

[0025] On the other hand, the present invention also provides a wire mesh-supported noble metal catalyst prepared by the above method.

[0026] Preferably, the wire mesh-supported noble metal catalyst is used in catalytic hydrogen combustion reactions.

[0027] Preferably, the wire mesh-supported noble metal catalyst is used in a catalytic hydrogen combustion reaction, wherein the hydrogen conversion rate in the catalytic hydrogen combustion reaction is ≥94.4%, and preferably the hydrogen conversion rate is 100%.

[0028] Preferably, the wire mesh-supported precious metal catalyst is used in a catalytic hydrogen combustion reaction, wherein the catalyst bed outlet temperature in the catalytic hydrogen combustion reaction is ≥65.4°C, and preferably the catalyst bed outlet temperature is greater than or equal to 100°C.

[0029] Preferably, the wire mesh-supported noble metal catalyst is used in a catalytic hydrogen combustion reaction, wherein the catalytic hydrogen combustion reaction is carried out at normal pressure, the space velocity of the reaction gas is 5000-50000h-1, and the volume fraction of hydrogen in the reaction gas is 1%-12%.

[0030] Preferably, the wire mesh-supported noble metal catalyst is used in a catalytic hydrogen combustion reaction, and the catalytic hydrogen combustion reaction can be applied to the fields of industrial, commercial and residential heating.

[0031] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention utilizes the ALD method to prepare a wire mesh-loaded noble metal catalyst, the deposition parameters are precisely controllable, and the deposition uniformity and repeatability are good.

[0034] The deposition parameters include reaction temperature, flow rate and introduction time of noble metal precursor, flow rate and purge time of inert gas, and flow rate and introduction time of oxidizing gas. The reaction temperature is controlled by the reactor temperature control system with an accuracy of ±0.05°C; the flow rate and introduction time of noble metal precursor, inert gas and oxidizing gas are controlled by a precision mass and time control system with a flow error of ±0.01mL / min and a time error of ±0.1ms.

[0035] The deposition uniformity is good, and the ALD method has the technical feature of self-limitation. In the present invention, it means that the precious metal precursor only reacts with the oxidizing species on the surface of the metal wire mesh. When all the oxidizing species are consumed by the reaction, the reaction stops automatically, and then the introduced oxidizing gas molecules react with the monomolecular layer of compounds containing precious metal components to form a monomolecular layer of precious metal oxide on the surface of the metal wire mesh. Therefore, the deposited precious metal oxide presents a uniform texture, so the deposition uniformity is good.

[0036] However, due to the huge difference in physical scale between the metal wire and the single-molecule layer of precious metal oxide, the diameter of the metal wire of the former is micrometer to millimeter level, while the scale of the single-molecule layer of precious metal oxide is sub-nanometer to nanometer level. At present, there is no electron microscope technology that can focus and distinguish the two at the same time. The present invention uses the technical principle of ALD to produce a wire mesh-supported catalyst. The obtained catalyst has excellent performance in the hydrogen combustion reaction, which fully reflects the scientificity, creativity and novelty of the present invention.

[0037] The good deposition repeatability means that each deposition cycle completely repeats the steps of the previous cycle, and each deposition cycle can only form one layer of molecular precious metal oxide. Therefore, each layer of precious metal oxide obtained has exactly the same structure and properties, reflecting the characteristics of good repeatability.

[0038] The present invention adopts a metal wire mesh as a carrier. The metal wire mesh material has a high thermal conductivity, so that it has good heat transfer performance and is conducive to heat transfer. DETAILED DESCRIPTION

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.

[0040] Precious Metal Precursors

[0041] The noble metal precursor described in the present invention is an organic metal precursor, which is selected from at least one of trimethyl (methylcyclopentadienyl) platinum (IV), bis (acetylacetonate palladium, and bis (ethylcyclopentadienyl) ruthenium (II).

[0042] Oxidizing gases

[0043] The oxidizing gas of the present invention is at least one of ozone or oxygen.

[0044] Inert gas

[0045] The inert gas described in the present invention may be nitrogen, helium, neon, argon, etc., but is not limited thereto.

[0046] Reaction site

[0047] The reaction sites described in the present invention are oxygen-containing species existing on the surface of the metal wire. Any metal placed in the air will form oxygen-containing species on the surface. These oxygen-containing species have chemical reaction capabilities and can be called reaction sites. One oxygen-containing species is one reaction site.

[0048] In the present invention, the noble metal precursor reacts with oxygen-containing species on the surface of the metal wire at 250°C to form a monolayer compound containing a noble metal component, and such compound reacts chemically with oxidizing gas molecules to form a monolayer of noble metal oxide, and the noble metal oxide can become a reaction site for the noble metal precursor added in the next cycle, reacting to form a second layer of noble metal compound, and then oxidized again to form a noble metal oxide. By repeating this cycle, a multilayer of noble metal oxide can be obtained.

[0049] The present invention utilizes oxygen-containing species existing on the surface of a metal wire placed in the air as reaction sites, and based on the ALD technical principle, successfully deposits noble metal oxides on the surface of the metal wire to produce a highly active hydrogen combustion catalyst, which is extremely creative.

[0050] Catalytic hydrogen combustion reaction

[0051] The catalytic hydrogen combustion reaction of the present invention is to introduce hydrogen and air into a reactor equipped with the wire mesh-supported noble metal catalyst provided by the present invention to carry out catalytic combustion reaction. The wire mesh-supported noble metal catalyst provided by the present invention can achieve high hydrogen conversion rate and high heat transfer efficiency.

[0052] In some embodiments, the volume fraction of hydrogen in the reaction gas is 1%-12%.

[0053] In some embodiments, the catalytic combustion reaction gas space velocity is 5000-50000h -1 .

[0054] In some embodiments, the catalytic combustion reaction is carried out at normal pressure.

[0055] Accordingly, the present invention provides a catalyst that can be used for hydrogen combustion reaction and a preparation method and a use method thereof.

[0056] As used herein, the term "about" refers to an amount, level, value, dimension, size, or amount that differs by up to 30%, 20%, or 10% compared to the amount, level, value, dimension, size, or amount of a reference product. Percentages used herein, unless otherwise indicated, are by weight.

[0057] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.

[0058] Experimental Materials:

[0059] Table 1:

[0060]

[0061]

[0062] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0063] Example 1: Preparation of wire mesh-supported noble metal catalyst

[0064] The ALD reactor was used to deposit Pt oxide on an aluminum mesh carrier. A 100mm×100mm×0.2mm, 100-mesh aluminum mesh (Al) was used as a carrier and placed in an ALD reactor. The reactor temperature was raised to 250°C and kept stable. 1g of the noble metal precursor trimethyl(methylcyclopentadienyl)platinum(IV) was heated and the generated vapor was introduced into the ALD reactor for 10-15s at a flow rate of 10mL / min. Then use ultrapure nitrogen at a flow rate of 500mL / min to purge away excess precious metal precursors that have not undergone chemical reactions, as well as by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. Check whether there are precious metal precursors and reaction by-products in the gas discharged in the early stage of purge. If so, it indicates that the reaction is saturated and excess precious metal precursors are discharged by the purge gas. Then check whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone in the gas discharged in the later stage of purge. If not, it can be determined that the purge is complete.

[0065] Oxidizing gas ozone (O3) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0066] The above steps constitute one cycle of the deposition process. The above cycle was repeated 4 times (5 cycles in total), and finally the aluminum wire mesh-supported Pt metal catalyst Pt5 / Al was prepared.

[0067] Test Example 1: Platinum loading of aluminum wire mesh-supported platinum metal catalyst

[0068] Test sample: The aluminum wire mesh supported Pt metal catalyst Pt5 / Al prepared in Example 1 was measured by inductively coupled plasma emission spectrometry (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0069] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0070] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0071] (Note: The testing process and results are implemented and provided by a third-party testing agency, such as but not limited to Shanghai Quality Supervision, Inspection and Technical Research Institute)

[0072] Table 2: Loading amount and cycle number of Pt metal catalyst supported on aluminum mesh

[0073] Cycle times Loading amount of Pt metal catalyst supported on aluminum mesh After 1 time 0.0016% After 2 times 0.0032% After 3 times 0.0048% After 4 times 0.0064% After 5 times 0.008%

[0074] As can be seen from the above table, after the preparation steps in Example 1 are cycled 5 times, the loading amount of the Pt metal catalyst loaded on the aluminum wire mesh is measured to be 0.008%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.0016% of Pt by mass can be deposited on the aluminum wire mesh in each cycle. Therefore, the number of cycles in Example 1 can be determined according to the required amount of deposition. That is, the preparation steps in Example 1 are one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of cycle repetitions. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursors is determined by the number of reaction sites on the surface of the carrier (aluminum wire mesh). Injecting excess precursors can ensure that the precursors occupy all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0075] Example 2: Preparation of stainless steel wire mesh loaded with precious metal catalyst

[0076] The ALD reactor was used to deposit Pt oxide on a stainless steel mesh carrier. A 100 mm × 100 mm × 0.2 mm, 50-mesh stainless steel mesh (SS) was placed in the ALD reactor, and the reactor temperature was raised to 250°C and kept stable; 1 g of the noble metal precursor trimethyl (methylcyclopentadienyl) platinum (IV) was heated, and the generated steam was introduced into the ALD reactor for 10-15 seconds at a flow rate of 10 mL / min. Then, ultrapure nitrogen with a flow rate of 500mL / min is used to purge away the excess precious metal precursor that has not undergone chemical reaction, as well as the by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. The gas discharged in the early stage of purge is tested to see whether there are precious metal precursors and reaction by-products. If so, it indicates that the reaction is saturated and the excess precious metal precursor is discharged by the purge gas. Then, the gas discharged in the later stage of purge is tested to see whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone. If not, it can be determined that the purge is complete.

[0077] Oxidizing gas ozone (O3) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0078] The above steps constitute one cycle of the deposition process. The above steps are repeated 9 times (10 cycles in total), and finally a stainless steel wire mesh-supported platinum metal catalyst Pt10 / SS is prepared.

[0079] Test Example 2: Platinum loading of stainless steel wire mesh-supported platinum metal catalyst

[0080] Test sample: The stainless steel wire mesh supported platinum metal catalyst Pt10 / SS prepared in Example 2 was analyzed using an inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, with a mass detection limit of up to 10-9 (ppb level)).

[0081] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0082] (Note: There are two facts that need to be explained. First, the ALD catalyst preparation process and the metal loading test process cannot be carried out simultaneously. The inductively coupled plasma emission spectroscopy test method is a destructive test method, and the sample cannot be recovered or reused after the test. The ALD catalyst preparation process needs to be carried out continuously. If it is interrupted once, there will be great losses in all aspects. Therefore, under normal circumstances, the experimental preparation process will not be interrupted to extract samples for analysis. Second, in order to establish the relationship between the number of ALD cycles and the metal loading, 2-3 samples are generally extracted during the experimental preparation process for analysis and testing to obtain the average loading of each deposition. For example, the experiment is interrupted after 2 cycles, and samples are taken for analysis; then everything starts from the beginning, and the experiment is interrupted after 5 cycles, and samples are taken for analysis; then it starts from the beginning, and so on. Since the ALD method has the characteristics of good repeatability (this is recognized by the industry and determined by its principle), therefore, as long as the loading of one cycle is mastered, the required number of cycles can be inferred based on the required metal loading, instead of measuring the metal loading for each cycle. The same applies below.)

[0083] After 10 cycles of the preparation steps in Example 2, the loading amount of the Pt metal catalyst loaded on the stainless steel wire mesh was determined to be 0.01%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.001% of Pt by mass can be deposited on the stainless steel wire mesh in each cycle. Therefore, the number of cycles in Example 2 can be determined according to the required amount of deposition. That is, the preparation steps in Example 2 are one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of repetitions of the cycle. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursors is determined by the number of reaction sites on the surface of the carrier (stainless steel wire mesh). Injecting excess precursors can ensure that the precursors occupy all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0084] Example 3: Preparation of nickel wire mesh supported noble metal catalyst

[0085] The ALD reactor was used to deposit Pt oxide on a nickel mesh carrier. A 100mm×100mm×0.5mm, 200-mesh nickel mesh (Ni) was used as a carrier and placed in an ALD reactor. The reactor temperature was raised to 250°C and kept stable. 1g of the noble metal precursor trimethyl(methylcyclopentadienyl)platinum(IV) was heated and the generated steam was introduced into the ALD reactor for 10-15s at a flow rate of 10mL / min. Then, ultrapure nitrogen with a flow rate of 500mL / min is used to purge away the excess precious metal precursor that has not undergone chemical reaction, as well as the by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. The gas discharged in the early stage of purge is tested to see whether there are precious metal precursors and reaction by-products. If so, it indicates that the reaction is saturated and the excess precious metal precursor is discharged by the purge gas. Then, the gas discharged in the later stage of purge is tested to see whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone. If not, it can be determined that the purge is complete.

[0086] Oxidizing gas ozone (O3) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0087] The above steps constitute one cycle of the deposition process. The above steps are repeated 19 times (a total of 20 cycles) to finally prepare the nickel wire mesh-supported platinum metal catalyst Pt20 / Ni.

[0088] Test Example 3: Platinum loading of nickel wire mesh-supported platinum metal catalyst

[0089] Test sample: The nickel wire mesh supported platinum metal catalyst Pt20 / Ni prepared in Example 3 was measured using an inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0090] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0091] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0092] Table 4: Loading amount and cycle number of nickel wire mesh supported Pt metal catalyst

[0093] Cycle times Loading amount of Pt metal catalyst supported on nickel wire mesh After 1 time 0.00075% 20 After this 0.015%

[0094] As can be seen from the above table, after 20 cycles of the preparation steps in Example 3, the loading amount of the Pt metal catalyst loaded on the nickel wire mesh was determined to be 0.015%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.00075% of Pt by mass can be deposited on the stainless steel wire mesh in each cycle. Therefore, the number of cycles in Example 3 can be determined according to the required amount of deposition. That is, the preparation steps in Example 3 are one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of cycle repetitions. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursors is determined by the number of reaction sites on the surface of the carrier (nickel wire mesh). Injecting excess precursors can ensure that the precursors occupy all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0095] Example 4: Preparation of Titanium Wire Mesh Supported Noble Metal Catalyst

[0096] The ALD reactor was used to deposit Pt oxide on the titanium mesh support. A 100mm×100mm×1mm, 10-mesh titanium mesh (Ti) was used as the support and placed in the ALD reactor. The reactor temperature was raised to 250°C and kept stable. 1g of the noble metal precursor trimethyl(methylcyclopentadienyl)platinum(IV) was heated and the generated steam was introduced into the ALD reactor for 10-15s at a flow rate of 10mL / min. Then, ultrapure nitrogen with a flow rate of 500mL / min is used to purge away the excess precious metal precursor that has not undergone chemical reaction, as well as the by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. The gas discharged in the early stage of purge is tested to see whether there are precious metal precursors and reaction by-products. If so, it indicates that the reaction is saturated and the excess precious metal precursor is discharged by the purge gas. Then, the gas discharged in the later stage of purge is tested to see whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone. If not, it can be determined that the purge is complete.

[0097] Oxidizing gas oxygen (O2) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0098] The above steps constitute one cycle of the deposition process. The above steps are repeated 29 times (30 cycles in total) to finally prepare the titanium wire mesh-supported platinum metal catalyst Pt30 / Ti.

[0099] Test Example 4: Platinum loading of titanium wire mesh-supported platinum metal catalyst

[0100] Test sample: Titanium wire mesh supported platinum metal catalyst Pt30 / Ti prepared in Example 4, using inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, mass detection limit can reach 10 -9 (ppb level)).

[0101] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0102] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0103] Table 5: Loading amount and cycle number of Pt metal catalyst supported on titanium mesh

[0104] Cycle times Loading amount of Pt metal catalyst supported on titanium mesh After 1 time 0.00067% 30 After this 0.02%

[0105] As can be seen from the above table, after 30 cycles of the preparation steps in Example 4, the loading amount of the Pt metal catalyst loaded on the titanium wire mesh was determined to be 0.02%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.00067% of Pt by mass can be deposited on the aluminum wire mesh in each cycle. Therefore, the number of cycles in Example 4 can be determined according to the required amount of deposition. That is, the preparation steps in Example 4 are one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of repetitions of the cycle. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursors is determined by the number of reaction sites on the surface of the carrier (titanium wire mesh). Injecting excess precursors can ensure that the precursors occupy all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0106] Example 5: Preparation of Silver Wire Mesh Supported Noble Metal Catalyst

[0107] The ALD reactor was used to deposit Pd oxide on the silver mesh carrier. A 100mm×100mm×0.1mm, 500-mesh silver mesh (Ag) was used as the carrier and placed in the ALD reactor. The reactor temperature was raised to 250°C and kept stable. 1g of the noble metal precursor diacetylacetonate palladium was heated and the generated vapor was introduced into the ALD reactor for 10-15s at a flow rate of 10mL / min. Then, ultrapure nitrogen with a flow rate of 500mL / min is used to purge away the excess precious metal precursor that has not undergone chemical reaction, as well as the by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. The gas discharged in the early stage of purge is tested to see whether there are precious metal precursors and reaction by-products. If so, it indicates that the reaction is saturated and the excess precious metal precursor is discharged by the purge gas. Then, the gas discharged in the later stage of purge is tested to see whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone. If not, it can be determined that the purge is complete.

[0108] Oxidizing gas ozone (O3) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0109] The above steps constitute one cycle of the deposition process. The above steps are repeated 39 times (40 cycles in total) to finally prepare the silver wire mesh-supported palladium metal catalyst Pd40 / Ag.

[0110] Test Example 5: Palladium loading of silver wire mesh-supported palladium metal catalyst

[0111] Test sample: The silver wire mesh supported palladium metal catalyst Pd40 / Ag prepared in Example 5 was measured by inductively coupled plasma emission spectrometry (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0112] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0113] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0114] Table 6: Loading amount and cycle number of silver wire mesh supported Pt metal catalyst

[0115] Cycle times Loading amount of Pt metal catalyst supported on silver wire mesh After 1 time 0.00075% 40 After this 0.03%

[0116] As can be seen from the above table, after 40 cycles of the preparation steps in Example 5, the loading amount of the Pt metal catalyst loaded on the titanium wire mesh was determined to be 0.03%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.00075% by mass of Pt can be deposited on the aluminum wire mesh in each cycle. Therefore, the number of cycles in Example 5 can be determined according to the required amount of deposition. That is, the preparation step in Example 5 is one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of repetitions of the cycle. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursor is determined by the number of reaction sites on the surface of the carrier (titanium wire mesh). Injecting excess precursor can ensure that the precursor occupies all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0117] Example 6: Preparation of copper wire mesh supported noble metal catalyst

[0118] Ru oxide was deposited on a copper mesh carrier using an ALD reactor. A 100mm×100mm×0.2mm, 250-mesh copper mesh (Cu) was placed in an ALD reactor, and the reactor temperature was raised to 250°C and kept stable; 2g of the noble metal precursor bis(ethylcyclopentadienyl)ruthenium(II) was heated, and the generated vapor was introduced into the ALD reactor for 10-15s at a flow rate of 10mL / min. Then, ultrapure nitrogen with a flow rate of 500mL / min is used to purge away the excess precious metal precursor that has not undergone chemical reaction, as well as the by-products CO2 and H2O produced by the reaction. The purge time is 25-30s. The gas discharged in the early stage of purge is tested to see whether there are precious metal precursors and reaction by-products. If so, it indicates that the reaction is saturated and the excess precious metal precursor is discharged by the purge gas. Then, the gas discharged in the later stage of purge is tested to see whether there are precious metal precursors and reaction by-products CO2 and H2O or ozone. If not, it can be determined that the purge is complete.

[0119] Oxidizing gas oxygen (O2) is introduced at a rate of 10 mL / min for 10-15 s to react with the monomolecular layer of precious metal compounds adsorbed on the surface of the metal wire to form a monomolecular layer of precious metal oxides; ultrapure nitrogen is then purged again at a flow rate of 500 mL / min for 25-30 s.

[0120] The above steps constitute one cycle of the deposition process. The above steps are repeated 49 times (50 cycles in total) to finally prepare the copper wire mesh-supported ruthenium metal catalyst Ru50 / Cu.

[0121] Test Example 6: Ruthenium loading of copper wire mesh-supported ruthenium metal catalyst

[0122] Test sample: The copper wire mesh supported ruthenium metal catalyst Ru50 / Cu prepared in Example 6 was measured by inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0123] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0124] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0125] Table 7: Loading amount and cycle number of Pt metal catalyst supported on copper wire mesh

[0126] Cycle times The loading amount of Pt metal catalyst supported on copper wire mesh After 1 time 0.001% 50 After this 0.05%

[0127] As can be seen from the above table, after 50 cycles of the preparation steps in Example 6, the loading amount of the Pt metal catalyst loaded on the copper wire mesh was determined to be 0.05%. The ALD method has the characteristics of good repeatability, which is reflected in the good linear relationship between the deposition amount of Pt metal and the number of cycles. Generally, 0.001% of Pt by mass can be deposited on the aluminum wire mesh in each cycle. Therefore, the number of cycles in Example 6 can be determined according to the required amount of deposition. That is, the preparation step in Example 6 is one cycle, and the thickness (size) of the deposited precious metal material can be controlled by controlling the number of repetitions of the cycle. Since ALD is a self-limiting adsorption reaction process, the amount of deposited precious metal precursor is determined by the number of reaction sites on the surface of the carrier (copper wire mesh). Injecting an excess of precursor can ensure that the precursor occupies all available reaction sites, so that the surface reaction sites reach application saturation in each cycle.

[0128] Example 7: Application of Aluminum Wire Mesh Supported Noble Metal Catalyst

[0129] The aluminum wire mesh-supported platinum metal catalyst Pt5 / Al sample (1.25 g) prepared in Example 1 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the fixed bed reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, wherein the volume fraction of hydrogen was 8%, and the space velocity of the mixed gas was 16000 h / min. -1 (Note: The space velocity is determined by the amount of catalyst used and the total flow rate). The raw materials of hydrogen and air are fed at room temperature (20°C) and reacted at normal pressure (1atm). After 1 hour, the gas composition at the outlet of the fixed bed reactor was measured, and the hydrogen conversion rate was calculated to be 94.4%. The outlet temperature of the catalyst bed was measured to be 65.4°C.

[0130] Example 8: Application of wire mesh-supported precious metal catalyst

[0131] The stainless steel wire mesh supported platinum metal catalyst Pt10 / SS sample (0.76 g) prepared in Example 2 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the fixed bed reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, wherein the volume fraction of hydrogen was 10%, and the gas space velocity was 30000 h / min. -1 (Note: The space velocity is determined by the amount of catalyst used and the total flow rate). The raw materials of hydrogen and air are at room temperature and react under normal pressure. After 1 hour, the gas composition at the outlet of the fixed bed reactor is measured, and the hydrogen conversion rate is calculated to be 96.2%. The outlet temperature of the catalyst bed is measured to be 102.3°C.

[0132] Example 9: Application of wire mesh-supported precious metal catalyst

[0133] The nickel wire mesh supported platinum metal catalyst Pt20 / Ni sample (0.38 g) prepared in Example 3 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, the volume fraction of hydrogen was 12%, and the gas space velocity was 50000 h / min. -1 (Note: The space velocity is determined by the amount of catalyst used and the total flow rate). The raw materials of hydrogen and air are at room temperature and react under normal pressure. After 1 hour, the gas composition at the outlet of the fixed bed reactor is measured, and the hydrogen conversion rate is calculated to be 98.1%. The outlet temperature of the catalyst bed is measured to be 176°C.

[0134] Example 10: Application of wire mesh-supported noble metal catalyst

[0135] The copper wire mesh supported ruthenium metal catalyst Ru50 / Cu sample (3.92 g) prepared in Example 6 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, the volume fraction of hydrogen was 1%, and the gas space velocity was 5000 h / min. -1 (Note: The space velocity is determined by the amount of catalyst used and the total flow rate). The raw materials of hydrogen and air are at room temperature and react under normal pressure. After 1 hour, the gas composition at the reactor outlet is measured and the hydrogen conversion rate is calculated to be 100%. The catalyst bed outlet temperature is measured to be 95.1°C.

[0136] Comparative Example 1: Preparation of wire mesh-supported noble metal catalyst

[0137] Pt oxide was loaded on the aluminum mesh carrier by impregnation. The chloroplatinic acid solid was dissolved in deionized water to prepare a chloroplatinic acid solution with a concentration of 0.01875 g / mL; a 100 mm × 100 mm × 0.2 mm, 100 mesh aluminum mesh was placed in 100 mL of chloroplatinic acid solution and stirred for 24 hours at a stirring rate of 600 rpm; after being taken out, it was placed in a blast oven at 120°C for 12 hours, and then placed in a muffle furnace for calcination at 600°C for 6 hours. After cooling, the Pt loading in the test sample was 0.00012%.

[0138] The above impregnation, drying and calcination steps were repeated 4 times to increase the Pt loading amount to obtain an aluminum wire mesh-supported platinum metal catalyst, and the Pt loading amount was measured in Test Example 7.

[0139] Test Example 7: Platinum loading of aluminum wire mesh-supported platinum metal catalyst

[0140] Test sample: Aluminum wire mesh supported platinum metal catalyst prepared in Comparative Example 1,

[0141] The inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0142] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0143] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0144] Table 8: Loading amount and cycle number of Pt metal catalyst supported on aluminum mesh

[0145] Cycle times Loading amount of Pt metal catalyst supported on aluminum mesh After 1 time 0.00012% After 5 times 0.00025%

[0146] As can be seen from the table above, after the preparation steps in Comparative Example 1 were cycled 5 times, the loading amount of the Pt metal catalyst supported on the aluminum wire mesh was measured to be 0.00025%. The impregnation method is not effective in loading precious metals on the aluminum wire mesh carrier. After the same preparation steps were cycled, the platinum loading amount of the aluminum wire mesh supported platinum metal catalyst prepared in Example 1 was 32 times that of the platinum loading amount of the aluminum wire mesh supported platinum metal catalyst prepared in Comparative Example 1. That is, the inventor unexpectedly discovered that the ALD method can not only realize the uniform and controllable loading of precious metal active components on the metal wire mesh, but also the loading amount of precious metals (such as platinum) has increased by dozens of times compared with the traditional impregnation method, which is of far-reaching significance.

[0147] Comparative Example 2: Application of wire mesh loaded precious metal catalyst

[0148] The aluminum wire mesh supported platinum metal catalyst sample (1.25 g) prepared in Comparative Example 1 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the fixed bed reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, the volume fraction of hydrogen was 8%, and the gas space velocity was 16000 h / min. -1 The raw material inlet temperature of hydrogen and air was 20°C, and the reaction was carried out under normal temperature and pressure. The gas composition at the outlet of the fixed bed reactor was measured after 1 hour, and the calculation results showed that hydrogen was basically not converted. The measured catalyst bed outlet temperature was 20°C, which was the same as the raw material inlet temperature.

[0149] Therefore, the aluminum wire mesh-supported platinum metal catalyst Pt5 / Al sample prepared in Example 1 and the aluminum wire mesh-supported platinum metal catalyst sample prepared in Comparative Example 1 were subjected to catalytic hydrogen combustion reaction under the same experimental conditions.

[0150] According to the hydrogen conversion rate and the measured catalyst bed outlet temperature, the aluminum wire mesh-loaded platinum metal catalyst Pt5 / Al sample prepared in Example 1 (the hydrogen conversion rate is 94.4% and the measured catalyst bed outlet temperature is 65.4°C) is better than the aluminum wire mesh-loaded platinum metal catalyst sample prepared in Comparative Example 1 (the hydrogen conversion rate is 0% and the measured catalyst bed outlet temperature is 20°C).

[0151] Comparative Example 3: Preparation of loaded noble metal catalyst

[0152] The ALD method is not used, nor is the metal mesh used to load the precious metal. The activated alumina balls (diameter 1-2mm, specific surface area 160m 2 / g) as a carrier, and an alumina-supported Pt catalyst was prepared by an impregnation method, the specific steps being as follows: dissolving chloroplatinic acid solid in deionized water to prepare a chloroplatinic acid solution with a concentration of 0.01875g / L; placing 1.25g of alumina pellets in 1.25mL of chloroplatinic acid solution and immersing and stirring for 24h at a stirring rate of 600rpm; taking out and placing in a blast oven at 120°C for 12h, and then placing in a muffle furnace and calcining at 600°C for 6h. After cooling, the alumina-supported noble metal catalyst was obtained and used for standby.

[0153] Test Example 8: Platinum loading of alumina-supported precious metal catalyst

[0154] Test sample: Alumina-supported noble metal catalyst prepared in Comparative Example 3,

[0155] The inductively coupled plasma emission spectrometer (PerkinElmer Optima 8300, USA, with a mass detection limit of 10 -9 (ppb level)).

[0156] Test process: Accurately weigh the sample mass, then put the sample into a polytetrafluoroethylene container, add 5mL concentrated nitric acid, 3mL concentrated hydrochloric acid, 1mL hydrofluoric acid, and 2mL hydrogen peroxide solution in sequence, then seal the polytetrafluoroethylene container, and then place it in a microwave digestion oven, heat it to 180°C at 1200W, and keep it for 40 minutes. Transfer the solution in the cooled polytetrafluoroethylene container to a 250mL plastic volumetric flask, dilute it with deionized water, and finally measure the Pt content in the solution by an inductively coupled plasma emission spectrometer to calculate the loading amount of Pt metal.

[0157] The loading amount of Pt metal = instrument reading × dilution factor × constant volume / sampling mass.

[0158] It was measured that the Pt loading of the alumina-supported noble metal catalyst prepared in Comparative Example 3 was 0.008%.

[0159] Comparative Example 4: Application of Alumina-supported Noble Metal Catalyst

[0160] The alumina-supported noble metal catalyst sample (1.25 g) prepared by the impregnation method in Comparative Example 3 was loaded into a fixed bed reactor, and hydrogen and air were introduced into the fixed bed reactor without premixing for catalytic combustion reaction. The total flow rate of hydrogen and air was 500 ml / min, the volume fraction of hydrogen was 8%, and the gas space velocity was 16000 h / min. -1The raw materials of hydrogen and air were fed at room temperature and reacted under normal pressure. The gas composition at the reactor outlet was measured after 1 hour, and the result showed that the hydrogen conversion rate was 51.4%. The outlet temperature of the catalyst bed was measured to be 34°C.

[0161] Thus, the aluminum wire mesh-supported platinum metal catalyst Pt5 / Al sample prepared in Example 1, the aluminum wire mesh-supported platinum metal catalyst sample prepared in Comparative Example 1, and the alumina-supported noble metal catalyst sample prepared in Comparative Example 3 were subjected to catalytic hydrogen combustion reaction under the same experimental conditions.

[0162] According to the hydrogen conversion rate and the measured catalyst bed outlet temperature, the aluminum wire mesh-loaded platinum metal catalyst Pt5 / Al sample prepared in Example 1 (the hydrogen conversion rate is 94.4% and the measured catalyst bed outlet temperature is 65.4°C) is better than the alumina-loaded precious metal catalyst sample prepared in Comparative Example 3 (the hydrogen conversion rate is 51.4% and the measured catalyst bed outlet temperature is 34°C), and is better than the aluminum wire mesh-loaded platinum metal catalyst sample prepared in Comparative Example 1 (the hydrogen conversion rate is 0% and the measured catalyst bed outlet temperature is 20°C).

Claims

1. A wire mesh-supported noble metal catalyst, characterized in that: The mass loading amount of the noble metal in the wire mesh is ≥0.008%.

2. The wire mesh-supported noble metal catalyst according to claim 1, characterized in that: The mesh number of the silk screen is 10-500 meshes, and the thickness is 0.1-1 mm; preferably, the mesh number is 50-250 meshes, and the thickness is 0.2-0.5 mm; more preferably, the mesh number is 100-200 meshes.

3. The wire mesh-supported noble metal catalyst according to claim 1, characterized in that: The wire mesh is woven from at least one metal wire selected from stainless steel, aluminum, copper, nickel, titanium or silver.

4. The wire mesh-supported noble metal catalyst according to claim 1, characterized in that: The noble metal is selected from at least one of platinum, palladium and ruthenium.

5. An atomic layer deposition method for preparing the wire mesh-supported noble metal catalyst as claimed in claim 1, comprising the following steps: (i) placing the screen in an atomic layer deposition reactor in advance, raising the temperature of the atomic layer deposition reactor to 250° C. and keeping it stable; (ii) heating the noble metal precursor and passing the generated vapor into the atomic layer deposition reactor for 10-15 seconds at a flow rate of 10 mL / min; (iii) using an inert gas at a flow rate of 500 mL / min to purge away the excess noble metal precursor that has not chemically reacted, as well as the byproducts CO2 and H2O generated by the reaction, for a purge time of 25-30 s; (iv) introducing an oxidizing gas at a flow rate of 10 mL / min for a time of 10-15 s; (v) purging again with an inert gas at a flow rate of 500 mL / min for a time of 25-30 s; (vi) Repeating steps (ii) to (v) several times in sequence to achieve layer-by-layer deposition of the noble metal oxide on the surface of the metal wire.

6. The method according to claim 5, characterized in that The wire mesh in step (i) is woven from at least one metal wire selected from stainless steel, aluminum, copper, nickel, titanium or silver.

7. The method according to claim 6, characterized in that The mesh number of the silk screen is 10-500 meshes and the thickness is 0.1-1 mm; preferably, the mesh number is 50-250 meshes and the thickness is 0.2-0.5 mm; more preferably, the mesh number is 100-200 meshes.

8. The method according to claim 5, characterized in that The noble metal is selected from at least one of platinum, palladium and ruthenium.

9. The method according to claim 5, characterized in that The noble metal precursor described in step (ii) is an organic metal precursor containing a noble metal component, and the organic metal precursor is selected from at least one of trimethyl (methylcyclopentadienyl) platinum (IV), bis (acetylacetonate palladium, and bis (ethylcyclopentadienyl) ruthenium (II).

10. The method according to claim 5, characterized in that The oxidizing gas in step (iv) is selected from at least one of ozone and oxygen.

11. The method according to claim 5, characterized in that The inert gas in step (iii) and step (v) is a high-purity gas with a volume concentration of 99.999%, and is selected from at least one of nitrogen, helium, neon, argon, etc.

12. The method according to claim 5, characterized in that The number of times steps (ii) to (v) are repeated in sequence in step (vi) is at least 5 times, preferably 5-50 times.

13. A wire mesh-supported noble metal catalyst prepared by the method according to any one of claims 5 to 12.

14. Use of the wire mesh-supported noble metal catalyst according to any one of claims 1 to 4 and claim 13 in catalytic hydrogen combustion reactions.

15. The use according to claim 14, characterized in that The hydrogen conversion rate in the catalytic hydrogen combustion reaction is ≥94.4%, and preferably the hydrogen conversion rate is 100%.

16. The use according to claim 14, characterized in that In the catalytic hydrogen combustion reaction, the catalyst bed outlet temperature is ≥65.4°C, and preferably the catalyst bed outlet temperature is greater than or equal to 100°C.

17. The use according to claim 14, characterized in that The catalytic hydrogen combustion reaction is carried out under normal pressure, and the space velocity of the reaction gas is 5000-50000h -1 , the volume fraction of hydrogen in the reaction gas is 1%-12%.

18. The use according to claim 14, characterized in that The catalytic hydrogen combustion reaction can be applied to industrial, commercial and residential heating and other fields.